1992
DOI: 10.1080/01972243.1992.9960121
|View full text |Cite
|
Sign up to set email alerts
|

Fragments of your communication: Email, vmail, and fax

Abstract: How are new media, such as electronic mail, voice mail, and fax, used when people have access to several of them simultaneously? This paper reports findings from a field study of media use in four sizable subunits within two large organizations where most employees had access to email, vmail, and fax. Respondents tended to use multiple electronic media rather than relying on one. However, they also showed a tendency to prefer one medium for asynchronous communication and to use the others for occasional, speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…Although Cerise members can ignore such notices, few do for long, especially when they are expecting a message. Social pressures are also brought to bear on e-mail use (see also Markus et al 1992). For example, one Cerise member, who also has an off-site office, was informally chided for only checking his e-mail four times a day.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Although Cerise members can ignore such notices, few do for long, especially when they are expecting a message. Social pressures are also brought to bear on e-mail use (see also Markus et al 1992). For example, one Cerise member, who also has an off-site office, was informally chided for only checking his e-mail four times a day.…”
Section: Discussionmentioning
confidence: 98%
“…Markus et al (1992) found that accessibility of the medium and of people via the medium (i.e., critical mass) and social pressures to conform to certain media use contributed to differences between organizations in the use of electronic mail, voice mail, and fax. Thus, group norms can dictate practice.…”
Section: Group Norms and Practicesmentioning
confidence: 97%
See 1 more Smart Citation
“…Other empirical research has compared and contrasted the new media (Rice, 1992;Adams, Nelson & Todd, 1993;Markus, Lynne, Bikson, El-Shinnawy & Soe, 1993;Soe & Markus, 1993). Except for Markus et al (1993) and Soe and Markus (1993) none of these studies examined alternative electronic media in the same organizational settings. In addition, none of the above studies explicitly employed the theoretical framework of MRT.…”
Section: Introductionmentioning
confidence: 93%
“…Because these analyses focus on individual-use technologies rather than interdependent ones, they typically do not take into account implementation processes in organizational environments in general or interdependency and critical mass among team members in particular. Therefore, our measures also rely on prior studies that are more socially or organizationally oriented (e.g., [4], [16], [17], [20], [21], [25], [32]). …”
Section: Introductionmentioning
confidence: 99%